Generalized holomorphic orthogonal function systems over infinite cylinders. (12th August 2014) - Morais, J.; Kou, K. I.; Le, H. T.
<x xml:space="preserve">Abstract</x> In this paper we construct two distinct generalized holomorphic orthogonal function systems over infinite cylinders in <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgj1qck434s" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />R3</alternatives>. Explicit representation formulae and properties of the obtained basis functions are given. As an application, we present some plot simulations that illustrate the results of this work. Copyright © 2014 John Wiley & Sons, Ltd.